Growth performance and bioremediation potential of Gracilaria gracilis (Steentoft, L.M. Irvine & Farnham, 1995). Issue 4 (4th July 2022) - Spanò, Nunziacarla; Di Paola, Davide; Albano, Marco; Manganaro, Antonio; Sanfilippo, Marilena; D'Iglio, Claudio; Capillo, Gioele; Savoca, Serena
ABSTRACT: The rapid development of aquaculture makes it desirable to use environment-friendly methods of purifying the wastewater effluent. Seaweed is often cultured for the dual purpose of useful algal biomass production and its bioremediation potential. This paper offers a survey on growth characters and ecological functions of the macroalgae Gracilaria gracilis (Steentoft, L.M. Irvine & Farnham, 1995), collected from Ganzirri lagoon (Messina, Italy). The results obtained provided promising data in terms of growth rates, biomass and biofiltering potential of G. gracilis . A daily growth rate (DGR) of 0.70%/g and biomass 36, 05 g/m 3 was obtained using tanks with lower lighting. Its biofiltration efficiency was demonstrated by the strong correlation between the algal growth parameters (Y and DGR) and the concentration decrease of dissolved nutrients. Results provided in this study indicated that G. gracilis can find application in aquaculture systems as a biofilter and that biomass produced offers a valid resource for further biotechnological applications.